How single-cell genomics is changing evolutionary and developmental biology - Marioni, John C.; Arendt, Detlev (Annual review of cell and developmental biology, 2017)
The recent flood of single-cell data not only boosts our knowledge of cells and cell types, but also provides new insight into development and evolution from a cellular perspective. For example, assaying the genomes of multiple cells during development reveals developmental lineage trees—the kinship lineage—whereas cellular transcriptomes inform us about the regulatory state of cells and their gradual restriction in potency—the Waddington lineage. Beyond that, the comparison of single-cell data across species allows evolutionary changes to be tracked at all stages of development from the zygote, via different kinds of stem cells, to the differentiating cells. We discuss recent insights into the evolution of stem cells and initial attempts to reconstruct the evolutionary cell type tree of the mammalian forebrain, for example, by the comparative analysis of neuron types in the mesencephalic floor. These studies illustrate the immense potential of single-cell genomics to open up a new era in developmental and evolutionary research.